2012
DOI: 10.1063/1.4766957
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting picosecond acoustics in the case of low interface stiffness

Abstract: Analysis of data acquired in time-domain thermoreflectance (TDTR) experiments requires accurate measurements of the thickness of the metal film optical transducer that absorbs energy from the pump optical pulse and provides a temperature dependent reflectivity that is interrogated by the probe optical pulse. This thickness measurement is typically accomplished using picosecond acoustics. The presence of contaminants and native oxides at the interface between the sample and transducer often produce a picosecond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 14 publications
2
51
0
Order By: Relevance
“…On Si, the Ta film was deposited slightly below 600°C to prevent the formation of an extensive Ta-Si silicide layer at the interface. Picosecond acoustics 16,35 and Rutherford backscattering spectroscopy confirmed that TaSi 2 or Ta 2 O 5 layers of appreciable thickness were not formed. For control experiments, Al and Ta films were also deposited on Si wafers that had 105 nm layers of thermal oxide on the surface, and Al films were deposited on single crystal Al, Cu, and Ni substrates, see Supplementary Fig.…”
Section: Methodsmentioning
confidence: 77%
“…On Si, the Ta film was deposited slightly below 600°C to prevent the formation of an extensive Ta-Si silicide layer at the interface. Picosecond acoustics 16,35 and Rutherford backscattering spectroscopy confirmed that TaSi 2 or Ta 2 O 5 layers of appreciable thickness were not formed. For control experiments, Al and Ta films were also deposited on Si wafers that had 105 nm layers of thermal oxide on the surface, and Al films were deposited on single crystal Al, Cu, and Ni substrates, see Supplementary Fig.…”
Section: Methodsmentioning
confidence: 77%
“…The native oxide of Si, SiOx, generally has a weak effect on picosecond acoustics. [21] The echo at 50 ps is the reflection at the BP/substrate interface. Although the acoustic impedance of BP is smaller than Si, we do not expect an intimately bonded interface between BP and Si, as there is finite 6 roughness for both the exfoliated BP surface and Si substrate.…”
mentioning
confidence: 99%
“…If the medium underneath has a smaller Z, then the acoustic echo undergoes a π-phase shift. [21] Picosecond acoustics data for a 55 nm thick BP sample are compared to those for the substrate in Figure 3A. The first upward echo at 28 ps that repeats periodically is a combination of the reflections from the NbV/AlOx and AlOx/BP interfaces having a similarly large contrast in Z (see Table S1).…”
mentioning
confidence: 99%
“…In the case of the Al film, we were also able to confirm the film thicknesses of most films with picosecond acoustics. 28,29 We report an uncertainty in transducer film thickness of 3 nm. An illustration of sample geometries studied in this work is shown in Fig.…”
Section: Gallium Oxide Fabrication and Chemical Characterizationmentioning
confidence: 81%